2022
DOI: 10.1002/dneu.22892
|View full text |Cite
|
Sign up to set email alerts
|

The role of snare proteins in cortical development

Abstract: Neural communication in the adult nervous system is mediated primarily through chemical synapses, where action potentials elicit Ca 2+ signals, which trigger vesicular fusion and neurotransmitter release in the presynaptic compartment. At early stages of development, the brain is shaped by communication via trophic factors and other extracellular signaling, and by contact-mediated cell-cell interactions including chemical synapses. The patterns of early neuronal impulses and spontaneous and regulated neurotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 203 publications
0
5
0
Order By: Relevance
“…The third component is a small sub-network centered around protein STX1A_ 1, SNAP25 _2, STXBP_ 1 and gene VAMP2. They are the major components of the SNARE complex, which medicates the fusion process of synaptic vesicles and play an essential role in the cross talk between neurons and glias [58, 59]. Top pathways enriched by these genes form a functional group related to release neurotransmitter cycle in Fig.3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third component is a small sub-network centered around protein STX1A_ 1, SNAP25 _2, STXBP_ 1 and gene VAMP2. They are the major components of the SNARE complex, which medicates the fusion process of synaptic vesicles and play an essential role in the cross talk between neurons and glias [58, 59]. Top pathways enriched by these genes form a functional group related to release neurotransmitter cycle in Fig.3.…”
Section: Resultsmentioning
confidence: 99%
“…These three functions together with STXBP1 to bring the membranes of synaptic vesicle and plasma membrane into apposition and to enable neurotransmission [58]. The SNARE complex is necessary not only for neuron–neuron communication but also neuron–glia and glia–glia communication [59].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated a critical role for neural activity during development in regulating synaptic connectivity (see [24, 61, 62] for reviews), providing a plausible link between BK channel GOF, excitatory neurotransmission, and an altered developmental state of pre-motor circuits that disrupts limb control. In support of this notion, stimulus-independent neural activity has been detected in the vertebrate developing spinal cord, and suppression of this activity results in a variety of defects in pre-motor circuit development and movement, including axonal mis-wiring [63], delayed onset of co-ordinated movement [64], and aberrant patterns of muscle activation [65].…”
Section: Discussionmentioning
confidence: 99%
“…SNARE complex in astrocytes is a four-helix-bundle protein consisting mainly of Synaptosomal-Associated Protein 23 (SNAP23), Syntaxin 4 (STX4), Vesicle-associated membrane protein 2 (VAMP2; also known as Synaptobrevin 2/SYB2), and Vesicle-associated membrane protein 3 (VAMP2; also known as Cellubrevin/CEB) that regulate synaptic vesicle exocytosis. The astroglial SNARE complex assembly forces the two membranes to fuse tightly with each other to regulate the timing of neurotransmitter release and initiate synaptic transmission ( Sutton et al, 1998 ; Südhof and Rothman, 2009 ; Vadisiute et al, 2022 ). This is achieved when vesicular and target membrane localized SNARE proteins zipper up into an alpha-helical bundle that merges both membranes generating the force for fusion ( Südhof and Rothman, 2009 ).…”
Section: Physiological and Pathophysiological Regulation Of Neurotran...mentioning
confidence: 99%
“…Interestingly, when astrocytes were injected with the light chain of the neurotoxin Botulinum B to selectively cleave VAMP, it resulted in the inhibition of the astrocyte-induced Glu response in neurons ( Araque et al, 2000 ). Despite this understanding, the function of SNARE proteins in astrocytes are still not well established and needs further research ( Vadisiute et al, 2022 ). The signaling molecules that glia release are ATP ( Halassa et al, 2009 ; Koizumi, 2022 ), lactic acid ( Suzuki et al, 2011 ), glutamic acid, as well as the non-synaptic release of acetylcholine (ACh) & prostaglandin E2 (PGE2; Araque et al, 1999 ), Glycine (Gly), gamma amino butyric acid (GABA; Benarroch, 2011 ), and D-Ser ( Henneberger et al, 2010 ).…”
Section: Physiological and Pathophysiological Regulation Of Neurotran...mentioning
confidence: 99%